Potential effects of power delegitimation: the attempt of methodological revision - Vinnykova, N. («East West» Association for Advanced Studies and Higher Education, 2017)
The article presents a methodological attempt to identify the forms of power delegitimation and the accompanying consequences in terms of the political decision-making. By employing such analytical categories as legitimacy and political networks this paper aims to determine the conditions under which the delegitimation may transform into its extreme form, i. e. a legitimacy rupture, and the repercussions, which will follow it.
Keywords: legitimacy, delegitimation, power, political decisions, political networks; legitimacy, delegitimation, power, political decisions, political networks